2009
DOI: 10.1111/j.1467-7687.2009.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear epigenetic variance: review and simulations

Abstract: We present a review of empirical evidence that suggests that a substantial portion of phenotypic variance is due to nonlinear (epigenetic) processes during ontogenesis. The role of such processes as a source of phenotypic variance in human behaviour genetic studies is not fully appreciated. In addition to our review, we present simulation studies of nonlinear epigenetic variance using a computational model of neuronal network development. In each simulation study, time series for monozygotic and dizygotic twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 62 publications
(136 reference statements)
1
27
0
1
Order By: Relevance
“…It resembles noise, and has its origins in nonlinear feedback [51,130]. Moreover, delays in feedback loops may interact with noise to generate oscillations in gene expression [131].…”
Section: Deterministic Chaosmentioning
confidence: 99%
“…It resembles noise, and has its origins in nonlinear feedback [51,130]. Moreover, delays in feedback loops may interact with noise to generate oscillations in gene expression [131].…”
Section: Deterministic Chaosmentioning
confidence: 99%
“…First, stochastic intra-individual developmental noise can lead to inter-individual differences in genetic and environmental influences as a third source, which however cannot be distinguished from non-shared environmental influences in conventional behavioural genetic studies (e.g., Molenaar et al 1993;Molenaar and Raijmakers 1999). Second, epigenetic processes (e.g., DNA methylation) involving interactions between genes, environment, and other processes could also affect gene expression to lead to interindividual heterogeneity (e.g., Bell and Saffery 2012;Bell and Spector 2011;Dolan et al 2015;Fraga et al 2005;Kan et al 2010;Petronis 2010;Wright et al 2014). These person-specific non-shared environmental influences offer a unique angle to examine twin concordance, not in their phenotypes per se (e.g., levels of happiness), but in their respective individual patterns of how nonshared environment influences them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, behavioural genetic studies adopting mixture modelling have demonstrated population heterogeneity regarding genetic and environmental influences (e.g., Eaves et al 1993;Gillespie and Neale 2006;Muthén et al 2006;Neale 2014). Stochastic intra-individual developmental noise (e.g., Molenaar et al 1993;Molenaar and Raijmakers 1999), gene expression and epigenetic processes (e.g., DNA methylation) can also result in substantial inter-individual differences in genetic and environmental influences (e.g., Bell and Saffery 2012;Bell and Spector 2011;Dolan et al 2015;Fraga et al 2005;Kan et al 2010;Petronis 2010;Wright et al 2014). Therefore, investigation of intra-individual variability could potentially provide unique and important information regarding genetic and environmental influences on intra-individual developmental processes that conventional behavioural genetic studies focusing on inter-individual differences could not offer, especially at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear interactions among multiple genes or between genes and environments can produce unpredictability in outcomes even in completely deterministic processes. 18 The second reason is that the tools that would be most useful in breaking down the complexity of development-random assignment to experimental condition and subsequent dissection of sacrificed individuals-are unavailable to human researchers and will forever remain so, once again for reasons having nothing to do with science. The possibility of genetic prediction of behavior fascinates because it leads to the edge of the possible in scientific psychology.…”
Section: Generating a Prediction From A Genome Is A Matter Of Figurinmentioning
confidence: 99%